Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

proove that

Asked by 14th March 2009, 4:32 PM
Answered by Expert
Answer:

Let that the angle bisectors of the said angles meet at P and ACD be the exterior angle of  the base angle C.

So,

 in triangle PBC,

angle PBC=1/2(B)...(as BP is the bisector of angle ABC)

angle PCB

=PCA+ACB

=1/2(angleACD)+C

=1/2(180-C)+C

=90-(C/2)+C

=90+(C/2)

So using angle sum property for triangle BPC, we get,

P+PBC+PCB=180

So,

P+1/2(B)+90+(C/2)=180

So,

P+[(B+C)/2]=90

So,

P+[(180-A)/2]=90.. (as B+C=180-A)

So,

P+90-(A/2)=90

So,

P=A/2

Hence proved.

Answered by Expert 14th March 2009, 6:31 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp